Implant retainers for free‐end removable partial dentures affect mastication and nutrient intake. Issue 8 (8th April 2013) - Campos, Camila Heitor; Gonçalves, Thais Marques Simek Vega; Rodrigues Garcia, Renata Cunha Matheus
Abstract Objectives This study measured swallowing threshold parameters and nutrient intake in partially dentate subjects rehabilitated by conventional free‐end removable partial dentures (RPD) and by RPD over posterior implant retainers and ball attachments (BA). Materials and methods Eight subjects (two men and six women; mean age 60.1 ± 6.6 years old) received conventional total maxillary dentures and free‐end RPD in the mandible. Two months after denture insertion, swallowing threshold and nutrient intake assessments occurred, which included an evaluation of the number of masticatory cycles and medium particle size (X50) of a silicone test material (Optocal). A 3‐day food diary verified nutrient intake based on a standard Brazilian Food Composition Table. Then, osseointegrated implants were placed bilaterally in the mandibular first molar region, followed by BA, which was fitted in the RPD bases after healing. After 2 months of the RPD over implants and BA use, variables were again assessed. Wilcoxon signed rank tests evaluated the data (P < 0.05). Results Masticatory cycles did not differ (P > 0.05); however, subjects showed decreased X50 values at the swallowing moment (P = 0.008) and increased daily energy (P = 0.008), carbohydrate (P = 0.016), protein (P = 0.023), calcium (P = 0.008), fiber (P = 0.016), and iron (P = 0.016) intake with RPD implants and BA inserts. No differences were found in fat consumption (P > 0.05). Conclusion Implants and BA retainers over a free‐end RPD resulted in smaller swallowed median particle size and improved nutrient intake.